Complex mixtures of Pesticides in Midwest U.S. streams indicated by POCIS time-integrating samplers. (January 2017) - Van Metre, Peter C.; Alvarez, David A.; Mahler, Barbara J.; Nowell, Lisa; Sandstrom, Mark; Moran, Patrick
Abstract: The Midwest United States is an intensely agricultural region where pesticides in streams pose risks to aquatic biota, but temporal variability in pesticide concentrations makes characterization of their exposure to organisms challenging. To compensate for the effects of temporal variability, we deployed polar organic chemical integrative samplers (POCIS) in 100 small streams across the Midwest for about 5 weeks during summer 2013 and analyzed the extracts for 227 pesticide compounds. Analysis of water samples collected weekly for pesticides during POCIS deployment allowed for comparison of POCIS results with periodic water-sampling results. The median number of pesticides detected in POCIS extracts was 62, and 141 compounds were detected at least once, indicating a high level of pesticide contamination of streams in the region. Sixty-five of the 141 compounds detected were pesticide degradates. Mean water concentrations estimated using published POCIS sampling rates strongly correlated with means of weekly water samples collected concurrently, however, the POCIS-estimated concentrations generally were lower than the measured water concentrations. Summed herbicide concentrations (units of ng/POCIS) were greater at agricultural sites than at urban sites but summed concentrations of insecticides and fungicides were greater at urban sites. Consistent with these differences, summed concentrations of herbicides correlate to percent cultivated crops in the watersheds and summed concentrations of insecticides and fungicides correlate to percent urban land use. With the exception of malathion concentrations at nine sites, POCIS-estimated water concentrations of pesticides were lower than aquatic-life benchmarks. The POCIS provide an alternative approach to traditional water sampling for characterizing chronic exposure to pesticides in streams across the Midwest region. Graphical abstract: Highlights: Pesticides are ubiquitous in small Midwest U.S. streams. POCIS time-integrating samplers had a median of 62 compounds detected per stream. Pesticides in POCIS and concurrent water samples correlate strongly. Most POCIS-estimated water concentrations were lower than aquatic-life benchmarks. Abstract : Ubiquitous occurrence of pesticides in small Midwest U.S. streams was indicated by high detection frequencies in POCIS time-integrating samplers and water.